An Analysis of Students’ Engagament in Supplemental Blended Learning Activity (A Case Study at an English Club in Tasikmalaya) - Firman Maulana (Journal of English Education Program (JEEP), 2023)
This journal reports the students’ engagement in a supplemental blended learning activity of teaching English writing using WhatsApp Group application. This research was aimed to find out the reason of student engagement in supplemental blended learning activity of teaching English writing. Qualitative research was chosen under the case study approach because this study focused on the detailed description of the study. Three data collection techniques used in this study are observation, questionnaire and student’s journal. Observation was conducted by video recording of the learning activity during the session and transcribed it. Questionnaire was analyzed by generalizing the data through percentage computation, and the students’ journal was analyzed through open ended question. In this regard, the participants in this study were the seventh grade at one of junior high school in West Java. By referring to the observation, the writer concluded about the extent to which the student’s engagement in teaching learning process of blended learning that covered emotional engagement, behavioral engagement, and cognitive engagement. Moreover, most of the students engaged in teaching learning process behaviorally. Then, the questionnaire data shows that the students gave positive responses toward blended learning in teaching activity. Then, the student’s journal showed that student engagement can increase the desire to learn both online and face to face result. Finally, future researchers are recommended to carry out the research with similar topic quantitatively to underpin the finding of this study. Finally, a suggestion is addressed to English teacher and future researcher who intends to investigate student engagement in blended learning, particularly in supplemental blended learning.